Charge order and structure transformation of hydrated cesium cobaltates revealed by variable‐temperature 133Cs NMR spectroscopy. Issue 9 (25th August 2022) - Lin, Eugene C.; Chen, Ting‐Hao; Chen, Pin‐Chen; Liao, Ming‐Yuan
Abstract: Variable temperature 133 Cs‐NMR experiments were performed to probe the local environment of the cesium ions in hydrated cesium cobaltates (Cs0.2 CoO2 ·0.63H2 O) from 170 to 390 K. Temperature dependence of the chemical shifts and linewidths reveals two‐phase transitions at a temperature near 200 and 350 K. Three inequivalent cesium sites are observed as the temperature is reduced below 200 K, indicating restricted motion of the cesium ions and a tendency to electron localization on cobalt ions. The results provide evidence for a definite order of the cesium ions and the charge order of the cobalt ions in the CoO2 layers. Two inequivalent cesium sites with larger chemical shift differences are observed as the temperature is above 350 K, indicating a spectacular change in the space between the CoO2 planes, which provides evidence for the transition between the bilayer‐hydrated and monolayer‐hydrated structures. Abstract : The 133 Cs NMR spectroscopy was used to study the temperature dependence of Cs0.2 CoO2 ·0.63H2 O. Two phenomena were revealed: (1) the phase transition between the bilayer‐hydrated (BLH) and monolayer‐hydrated (MLH) structures above 350 K, and (2) the existence of the Co 4+ /Co 3+ charge order below 200 K.